1995
DOI: 10.1116/1.579652
|View full text |Cite
|
Sign up to set email alerts
|

The chemistry of a CCl2F2 radio frequency discharge

Abstract: A systematic study of the chemistry of stable molecules and radicals in a low pressure CCl 2 F 2 radio frequency discharge for dry Si etching has been performed. Various particle densities have been measured and modeled. The electron density, needed as an input parameter to model the CCl 2 F 2 dissociation, is measured by a microwave cavity method. The densities of stable molecules, like CClF 3 , CF 4 , 1,2-C 2 Cl 2 F 4 and the etch product SiF 4 , are measured by Fourier transform absorption spectroscopy. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…We use the fact that stable molecules are removed by the gas flow, 10 while the radical densities are flow independent. Thus, by comparing the spectra for different gas flow rates the radical absorption lines can be found.…”
Section: Identification Of the Spectra Of Cf Cf 2 And Cfmentioning
confidence: 99%
“…We use the fact that stable molecules are removed by the gas flow, 10 while the radical densities are flow independent. Thus, by comparing the spectra for different gas flow rates the radical absorption lines can be found.…”
Section: Identification Of the Spectra Of Cf Cf 2 And Cfmentioning
confidence: 99%
“…RF discharge plasmas have to be discerned from surface, silent, and glow discharge plasmas. Radio frequency (RF) plasmas favor electron impact dissociation over electron attachment dissociation as Stoffels et al observed for dissociation of CCl 2 F 2 (up to 90%) at low pressure (0−400 mTorr) and high power input. Wang et al showed for the same compound that high decomposition rates (up to 94%) and high selectivities to CH 4 and C 2 H 2 (up to 80%) are achievable in a low-pressure hydrogen−argon RF plasma system.…”
Section: Introductionmentioning
confidence: 99%
“…The main products of dissociation of CF 2 Cl 2 molecules are CF 2 Cl, CF 2 radicals, and Cl atoms [9]. In order to reduce the number of frequency probabilities that are freely chosen, only CF 2 radicals are considered.…”
Section: Modelmentioning
confidence: 99%